Profile Analysis of Creative Thinking Skills and Sustainability Awareness of Senior High School Students in Polewali Mandar Regency - Irawan*, Peri; Kaniawati, Ida; Sriyati, Siti (Universitas Syiah Kuala, 2024)
21st century skills are currently very important in the demands of student learning. However, some previous studies have shown that students have low levels of 21st century skills development. One of the important 21st century skills is creative thinking skills. In addition, in the current era, students must also have an awareness of sustainability, given the many natural phenomena that occur in their lives. This study aims to analyze the profile of the level of creative thinking skills and sustainability awareness in one of the senior high schools in Polewali Mandar Regency. This research is quantitative descriptive research conducted by giving a questionnaire of creative thinking skills and sustainability awareness. The questionnaire instrument was made as many as 15 statements, each of which had four alternative answers. The creative thinking skills questionnaire was made using four indicators namely fluency, flexibility, originality and elaboration, while sustainability awareness uses three indicators namely behavioral and attitudinal awareness, emotional awareness and practical awareness. The results showed that the profile of creative thinking skills in each indicator was 65% fluency in the moderate category, 74% flexibility in the creative category, 67% originality in the moderate category and 67% elaboration in the moderate category. As for the profile of student sustainability awareness on each indicator, namely behavioral and attitudinal awareness of 68% with the category of habits that are being carried out with a sufficient level, emotional awareness of 78% with the category of habits that always occur, and practical awareness of 59% with the category of habits that are being carried out with a sufficient level.